Encruzilhada atlântica: reconstruindo possibilidades de proteção aos territórios Sagrados das comunidades de matriz africana - Almeida, Jennifer Martins (2022)
This work has as a phenomenon the right to protect the sacred territories of traditional communities of African origin. It’s general aim to analyze, in the light of the critical theory of Human Rights and decolonial practice, the possibilities and limits of legal protection to the sacred territories of the communities of terreiro, considering the concepts of self-definition, identity and territoriality established in Convention 169 of the International Labor Organization (ILO) and the situation of legal uncertainty in the territory experienced by the Umbanda community “Filhos do Oriente Maior”, in the city of Açailândia/MA. It's about research qualitative, that having as support sources bibliographics, documents and the field research, developed at Centro Espiritualista Filhos do Oriente Maior, using semi-structured interviews as a data collection instrument. The theoretical framework adopted is aligned with decolonial thinking, not limited to thinkers of the modernity/coloniality group, understanding decoloniality as a project of deconstruction and reconstruction of knowledge that inverts the colonial logic of subalternizing, silencing and making invisible the knowledge produced by colonized peoples. Thus, we used the concept of amefricanities, listed by Lélia Gonzalez (2020), miscegenation, established by Kabengele Munanga (2020), myth of racial democracy, highlighted by Abdias Nascimento (2016), corporeality, outlined by Beatriz Nascimento (1989) and Luiz Rufino (2019). Finally, it was found that Modern Law, with a Eurocentric matrix, reproduces the coloniality of power, implying limitations in the application of legal instruments protecting the territorial rights of terreiro peoples, since communities of African origin are based on a cosmology different from the civility concepts of possession and property and the body/mind duality.